Idas y venidas de la cooperación internacional para el desarrollo - Pescador Hernández, Silvia (Revista Española de Desarrollo y Cooperación, 2023)
The following lines briefly review the main events that have taken place during the last months and their implications to the fight against poverty and inequality in the developing world. Attending to the new initiatives promoted by different actors, it tackles which are and will be in the short term the challenges that international cooperation must face.